(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2010)
Key words: dermoid; hard palate; bifid tongue DOI: 10.3329/jcmcta.v20i1.4938 Journal of Chittagong Medical College Teachers’ Association 2009: 20(1):58-60